Dexamethasone Activities toward Population of B cells, Gr-1, and TNF-Î± cytokine in Mice (Musmusculus) Balb/c Biliary Atresia Model - Rahmawati, Riza (Biotropika: Journal of Tropical Biology, 2014)
Biliary atresia iscondition caused by Rotavirus (RRV) infection. The aims of this study were to know the immune responses of mice model of biliary atresia treated with corticosteroid.Mice were splitinto 3 treatment groups: control (K), RRV injection (R), and RRV injection in the present of dexamethasone(R+D). In R treatment, the baby mice born in <24 hours were injected with 20 Âµl of phosphate buffered saline containing 1.5 x 106 fluorescence-forming units Rhesus Rotavirus (RRV). First termination was performed in the day 7 to 14, while second termination was done in the day 14 to 21. The dosage of dexamethasone which is applied in this experiment is 0.5mg/kg body weight.Immunocompetent cells were isolated from spleen,Â and cell surface molecules were then analyzed by flowcytometry. The data was tested by SPSS 16.0 for Windows program. The results showed that dexamethasone given as corticosteroid for biliarry atresia theurapy couldsuppress TNF-Î±production as well as Gr-1 proliferation. In the other hand dexamethasonecan promote B220+ cell proliferation inrotavirus infected mice. Key word: Baby mice, biliary atresia, dexamethason, flowcytometry, rotavirus